Currency Internationalization and Macro Financial Risk Control (Springer Singapore, 2018)
This book collects expert opinions, research, and risk assessments from within the Chinese financial policy establishment on prospects for the internationalization of the renminbi as a reserve currency around the world. As China's economy diversifies in the acquisition of global assets, the renminbi may partially displace the dollar or yen as a reserve currency, with unpredictable and profound potential consequences. This book, presenting for the first time in English, the Chinese perspective on the internationalization of the Chinese currency will be of great value to central bankers, financiers, and students of international finance. The International Monetary Institute at Renmin University is China's foremost think-tank on issues of currency internationalization, currency flows, central banking, and related topics. Research at the think-tank is conducted collectively by fellows and associates.